Atropine in Myopia - Priyanka Mishra; Rebika Dhiman; Bhavika Bansal; Rohit Saxena (Delhi Journal of Ophthalmology)
Myopia is emerging as a global public health problem with nearly half of the world’s population predicted to become myopic by 2050. Genetic factors along with evolving lifestyle modifications like reduced outdoor activity, increased screen time and near work have contributed to this surge. Of several therapies described for anti-myopia therapy, topical atropine is emerging as the most popular management option owing to the ease of administration and minimal side effects. Based on the effect versus side effect profile, 0.01% atropine appears to be the optimal concentration for reducing myopia progression. In this review, we discuss the effectiveness of atropine therapy, its side effects and indications of use in the light of the best available literature. Some questions like duration of therapy, role of higher dose of atropine in non-responders and role of combination therapy with other interventions like orthokeratology still needs to be explored.